Population Growth and Long-Distance Vagrancy Leads to Colonization of Europe by Elegant Terns Thalasseus elegans - Veit, Richard Reed; Velarde, Enriqueta; Horn, Michael H.; Manne, Lisa L. (Frontiers in Ecology and Evolution, 2021)
Elegant Terns Thalasseus elegans breed in a very limited area of the northern Gulf of California and the Pacific coast of southern California, with up to 95% (mean 78%, 1991-2014, Perez et al. 2020) of the population nesting on Isla Rasa in the northern Gulf of California. Elegant Terns winter on the Pacific coast from Mexico to Chile, but some travel north during late summer and fall, somewhat irregularly, to the Pacific Northwest. Elegant Terns, because of their close association with the Eastern Boundary Currents, such as the California Current off North America and the Humboldt or Peru Current off South America, have been repeatedly impacted by El Niño events that limit upwelling and result in catastrophic (though temporary) declines of the fishes upon which they feed. During most El Niño events, large numbers of Elegant terns deserted their colonies and, beginning in 1982-1983, also moved much farther north along the west coast of North America during summer and fall than they had done previously. On Isla Rasa, the primary nesting colony, Elegant Terns suffered predation by rodents which raised the possibility of population extinction, with a substantial proportion of the world population nesting on this single island. Because of this threat, rodents were successfully removed from Isla Rasa in 1995. The removal of rodents from Isla Rasa led to a near immediate increase in the population of Elegant Terns, and that increase was associated with a changing pattern in dispersal by the terns, including extraordinary movements to the Gulf of Mexico, the Atlantic coast of the United States north to Massachusetts, and to western Europe, where a few Elegant Terns successfully bred during 2009 to the present. In this paper we use this exceptional example of long-distance dispersal to illustrate how rapid population growth during 1995 to present can lead to successful colonization of remote sites. The “vagrancy” by Elegant Terns is similar to recent descriptions of “exploratory behavior”, “informed dispersal” and “intelligent dispersal” could be representative of how seabirds in particular, and organisms in general may be able to escape “climate extinction”.